Electrochemical Sensor based on Indium Tin Oxide Glass Modified with Poly(Ethyleneimine)/Phosphomolybdic Acid Composite Multilayers. Issue 4 (26th January 2017) - Hao, Yanjun; Feng, Shun; Liu, Yumei; Xu, Jie; Ma, Yuhua; Wang, Jide
Abstract: In this work, one novel electrochemical sensor was prepared by alternative deposition of phosphomolybdic acid (PMoA) and poly(ethyleneimine) (PEI) on an indium tin oxide glass substrate through layer‐by‐layer assembly. The performance of as‐prepared electrode was evaluated with both of oxidizing compounds of iodate and H2 O2 and reducing compounds of dopamine and ascorbic acid as models. The results showed that corresponding current response of redox peak increased linearly with the concentration of above compounds increasing in certain ranges, respectively. Limits of detection to them were in the range of 1.0×10 −4 ‐ 4.3×10 −4 mg mL −1 with cyclic voltammetry (CV) in 0.1 mol L −1 NaAc‐HAc buffer (pH 5.0). The electrode showed high stability and remained 95 % of its initial activity even after 100 cycles of CV scan. When applied in real samples of table salts, juice and human serum, high recoveries of 96.84 to 100.33 % were achieved with relative standard deviations of 1.11‐3.96 % (n=3) at three spiked levels. Moreover, it was also successfully applied for the simultaneous determination of dopamine and ascorbic acid in human serum with differential pulse voltammetry. The results indicated that PMoA/PEI multilayer modified electrode can be used as a universal electrochemical sensor for sensitive detection of redox compounds. Abstract :